Post-operative complications and ADHD - Yoon, YooJin; Kennis, Matthew; Hale, Elijah W. (Frontiers in Child and Adolescent Psychiatry, 2022)
ADHD is associated with a number of developmental, emotional, social, academic, and cognitive health risks that can affect the adolescents' quality of life. There have been various guidelines published regarding the management of children with ADHD, however, it has been reported that physicians may not adequately screen for ADHD prior to surgery. To our knowledge, there are no such studies studying post-operative complications and outcome rates in adolescents with ADHD. We conducted a retrospective case-control study through the TriNetX databases. We identified patients with ADHD (ICD-10: F90) undergoing a surgical procedure (CPT: 1003143), and a control group of non-ADHD patients undergoing a surgical procedure. From these two pairs of case-control cohorts we compared outcomes of post-procedural infections, post-procedural shock, and any post-procedural complications. We identified 791,481 matched pairs of subjects undergoing surgery where one of the pair had ADHD and the other did not. Among subjects undergoing a surgical procedure, those with ADHD had a significantly higher risk of post-procedural infection and any post-procedural complication, relative to subjects without ADHD. Furthermore, those with ADHD showed a heightened risk of post-procedural complications in all procedural subcategories. These novel findings suggest that ADHD is a notable factor in surgical care and should be given special consideration by both surgeons and psychiatrists.